Gender stereotypes in preschoolers’ mental rotation - Ebert, W. Miro; Jost, Leonardo; Jansen, Petra (Frontiers in Psychology, 2024)
The investigation of gender stereotypes constitutes a relevant approach to understanding the development of spatial ability and sex differences in the domain. This was the first study concerned with the presence of implicit and explicit gender stereotypes about spatial ability, and their potential relation to spatial task performance, in preschool-aged children. Our full sample consisted of 138 4-to 6-year-old kindergarten children. The experimental procedure consisted of three parts. Children completed an implicit association task, a short questionnaire on explicit stereotypes, and a chronometric mental rotation task. Preschool-aged children held explicit gender stereotypes about spatial ability linking it to boys rather than girls. Boys exhibited stronger stereotypes in this regard than girls. We also found evidence for the presence of implicit stereotypes. However, implicit stereotypes were not found in sub-group analyses. No clear relationship between stereotypes and mental rotation performance emerged, but our results suggest that implicit stereotyping affected mental rotation accuracy differently in girls compared with boys. Our main conclusion was that children already hold stereotypic beliefs about spatial ability at preschool age. There did not seem to be a relationship of stereotyping with spatial ability at this age.